Burnout syndrome in nursing professionals in a neonatal intensive therapy unit - Fernanda Gomes da Silva Silva, Vladimir Araújo da Silva, Julia Trevisan Martins, Miderson Andrei de Souza Santana, Beatriz Maria dos Santos Santiago Ribeiro (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/2238-7234.9159-64